2018
DOI: 10.1038/aps.2017.135
|View full text |Cite
|
Sign up to set email alerts
|

Schisandrin ameliorates cognitive impairment and attenuates Aβ deposition in APP/PS1 transgenic mice: involvement of adjusting neurotransmitters and their metabolite changes in the brain

Abstract: Neurotransmitters (NTs) in the brain are involved in neurodegenerative diseases, such as Alzheimer's disease (AD). Schisandrin is a major ingredient of Schisandra chinensis (Turcz.) Baill and has been used for the treatment of AD. In this study we examined the therapeutic effects of schisandrin in APP/PS1 transgenic mice, and correlated the beneficial effects on cognitive impairment with the adjustments in NTs and their metabolites in the mouse brains. APP/PS1 mice were treated with schisandrin (2 mg·kg·d, ip)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(19 citation statements)
references
References 26 publications
0
19
0
Order By: Relevance
“…In addition, it has been hypothesized that Aβ deposits in the olfactory system promote AD pathology in rodents (Wesson et al, 2010, 2011). In vivo , excessive Aβ depositions within the hippocampus lead to learning and memory deficits (Kim et al, 2013; Birnbaum et al, 2015; Lei et al, 2016; Wei et al, 2018). Similarly, Aβ depositions in the OB affected olfactory-related behavioral performances in APP/PS1 mice.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, it has been hypothesized that Aβ deposits in the olfactory system promote AD pathology in rodents (Wesson et al, 2010, 2011). In vivo , excessive Aβ depositions within the hippocampus lead to learning and memory deficits (Kim et al, 2013; Birnbaum et al, 2015; Lei et al, 2016; Wei et al, 2018). Similarly, Aβ depositions in the OB affected olfactory-related behavioral performances in APP/PS1 mice.…”
Section: Discussionmentioning
confidence: 99%
“…We additionally found that pretreatment with schizandrin could prevent H9c2 cells against an LPS‐induced inflammatory response. Actually, schizandrin has been involved in recent in vivo and in vitro pharmacological studies suggesting a protective effect in various pathological models including APP/PS1 transgenic mice, chronic unpredictable mild stress in mice, ovariectomized (OVX) and non‐OVX rats, TGF‐β1‐stimulated AML12 cells, and cisplatin‐stimulated HK‐2 cells . Our findings for the first time demonstrated that schizandrin could prevent LPS‐induced cell damage by influencing the release of inflammatory cytokines.…”
Section: Discussionmentioning
confidence: 58%
“…Preclinical studies have found the memory and learning deficits along with the observation of cerebral atrophy, amyloid plaques, and neurofibrillary tangles in STZ-treated rats [ 13 ]. Schisandrin has been suggested the potential to exert the neuroprotective effect on Alzheimer’s disease [ 27 ]. The Morris water maze test was performed in our study after the treatment of schisandrin.…”
Section: Discussionmentioning
confidence: 99%